ANALISIS TINJAUAN YURIDIS MENGENAI TINDAK PIDANA PIDANA PEMERKOSAAN PERLINDUNGAN HUKUM TERHADAP KORBAN - Nur Hidayah Hasibuan; M. Iraqi Fauzi, Mira Cahya, Reh Bungana Beru Perangin-angin, Maulana Ibrahim (ADISAM PUBLISHER, 2023)
The crime of rape is a form of violence against women which is an example of the vulnerability of women's position, especially to the sexual interests of men. The crime of rape is a form of violence against women which is an example of the vulnerability of women's position, especially to the sexual interests of men. Based on the results of the study, protection for victims of crimes against women includes preventive and repressive protection, as well as protection and supervision both in the investigation process and the health examination process, which is clearly stated in the statutory regulations issued by law enforcement officials that have been included. Tools to protect human rights. In addition to compensation measures, we can also provide legal assistance, reimbursement and compensation.